Hydrogen and carbon isotope fractionation during degradation of chloromethane by methylotrophic bacteria. Issue 6 (8th September 2013) - Nadalig, Thierry; Greule, Markus; Bringel, Françoise; Vuilleumier, Stéphane; Keppler, Frank
Abstract Chloromethane (CH3Cl) is a widely studied volatile halocarbon involved in the destruction of ozone in the stratosphere. Nevertheless, its global budget still remains debated. Stable isotope analysis is a powerful tool to constrain fluxes of chloromethane between various environmental compartments which involve a multiplicity of sources and sinks, and both biotic and abiotic processes. In this study, we measured hydrogen and carbon isotope fractionation of the remaining untransformed chloromethane following its degradation by methylotrophic bacterial strains Methylobacterium extorquens CM4 and Hyphomicrobium sp. MC1, which belong to different genera but both use the cmu pathway, the only pathway for bacterial degradation of chloromethane characterized so far. Hydrogen isotope fractionation for degradation of chloromethane was determined for the first time, and yielded enrichment factors (ε) of −29‰ and −27‰ for strains CM4 and MC1, respectively. In agreement with previous studies, enrichment in 13C of untransformed CH3Cl was also observed, and similar isotope enrichment factors (ε) of −41‰ and −38‰ were obtained for degradation of chloromethane by strains CM4 and MC1, respectively. These combined hydrogen and carbon isotopic data for bacterial degradation of chloromethane will contribute to refine models of the global atmospheric budget of chloromethane.